PREDICTION OF RADON CONCENTRATIONS IN ABOVE-GROUND APARTMENTS - Bakaeva, Natalia Vladimirovna; Kalaydo, Aleksandr Vitalyevich (Journal of Applied Engineering Science, 2017)
The estimate of radiation safety in existing buildings by indoor radon levels measuring requires considerable time and financial costs, at stage of the constructions design it is not possible generally. So the prediction of radon concentrations in new and existing buildings on the basis of mathematical modeling is the actual problem. The semi-empirical model of radon levels prediction in the above-ground apartments presents in the paper. The model structure is the result of theoretical studies of soil gas transport mechanism in a porous media and the empirical constants determined based on the radiation monitoring results of the buildings and territory of the University.
Keywords: Radiation safety; Progeny; Equivalent; Equilibrium; Radon; Concentration (EERC); Construction